Comparative Analysis of Personality Structures of the Perpetrators of Aggressive and Non-aggressive Offense - Kalashnikova A.S.; Vasilenko T.G., (Психологическая наука и образование (2007. Online), 2014)
problem of the emergence of aggressive behavior is seen through the analysis of the relationship of proagressive and inhibiting aggression personality structures. The study involved 54 men serving sentences for criminal offenses, of which 24 were accused for violent offenses and 30 - for offenses without resorting to violence. We used questionnaires to study the proagressive and deterring aggression personality structures. Statistical analysis was performed to reveal significant differences between groups and to determine correlations. On this basis, the correlations were interpreted with the help of not only quantitative but also qualitative analysis. The results showed no significant differences in the level of expression of aggression and aggression inhibitors between treatment groups, but we identified qualitative differences in the structural analysis of data from individual psychological characteristics that are expected to distinguish aggressive offenders from the perpetrators without violence.